P27 deficiency accelerates the development of PTEN-deficiency-induced myeloproliferative disease - Shao, Jingchen (My University, 2015)
PTEN acts as a phosphatase for PIP3 and negatively regulates the PI3K/AKT pathway, and CDKN1B (P27KIP1) is a cyclin-dependent kinase inhibitor that regulates G0 to S phase transitions by binding to and regulating the activity of cyclin-dependent kinases. Genetic alternations of Pten or Cdkn1b are common in hematological malignancies. Combined loss of PTEN and P27KIP1 expression is associated with tumor cell proliferation and poor prognosis in prostate cancer. However, it is not so clear how two mutations would cooperate in leukemogenesis. Here, we show that combined inactivation of PTEN or P27KIP1 in the hematopoietic compartment in mice results in a more severe myeloproliferative disease phenotype with shorter lifespan, lower hemoglobin and more enlarged spleen, lever comparted inaction of Pten or p27KIP1 alone.
Keywords: Livsvetenskaper; Biologiska vetenskaper; Bioinformatik och systembiologi; Life Science; Biological Sciences; Bioinformatics and Systems Biology